2021
DOI: 10.1002/adsc.202100523
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐Controlled Divergent Cascade Cycloaddition Reactions of Chalcones and Arylalkynols: Access to Spiroketals and Oxa‐Bridged Fused Heterocycles

Abstract: Herein, we report substituent‐controlled divergent cascade cycloaddition reactions of chalcones and arylalkynols in the presence of PtI2. Depending on the substituent on the chalcone, either spiroketals or oxa‐bridged fused heterocycles could be obtained in the ranges of 86–97% and 87–95% yields under identical reaction conditions. Control experiments were carried out to elucidate the origin of the high chemoselectivity. These provide a method for the synthesis of a diverse array of structurally complex oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…mp 50−52 °C. 1 H NMR (400 MHz, CDCl 3 ) δ 8.02 (dd, J = 7.6, 1.9 Hz, 1H), 7.93−7.85 (m, 2H), 7.55 (dd, J = 7.5, 5.7 Hz, 3H), 7.51 (dd, J = 6.6, 5.0 Hz, 1H), 7.34 (tdd, J = 7.3, 4.9, 1.9 Hz, 1H), 7.27−7.16 (m, 3H), 2.75 (s, 3H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 160.0 (d, 1 J C−F = 247.9 Hz), 134.4, 133.5, 132.9, 131.9, 131.0 (d, 3 2-(4-Methylnaphthalen-2-yl)thiophene (2m, New Compound). Flash chromatography of the crude reaction product (PE/EA = 50:1(v/v)) gave a white solid (27.3 mg, 61%).…”
Section: -(2-fluorophenyl)-1-methylnaphthalene (2i New Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…mp 50−52 °C. 1 H NMR (400 MHz, CDCl 3 ) δ 8.02 (dd, J = 7.6, 1.9 Hz, 1H), 7.93−7.85 (m, 2H), 7.55 (dd, J = 7.5, 5.7 Hz, 3H), 7.51 (dd, J = 6.6, 5.0 Hz, 1H), 7.34 (tdd, J = 7.3, 4.9, 1.9 Hz, 1H), 7.27−7.16 (m, 3H), 2.75 (s, 3H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 160.0 (d, 1 J C−F = 247.9 Hz), 134.4, 133.5, 132.9, 131.9, 131.0 (d, 3 2-(4-Methylnaphthalen-2-yl)thiophene (2m, New Compound). Flash chromatography of the crude reaction product (PE/EA = 50:1(v/v)) gave a white solid (27.3 mg, 61%).…”
Section: -(2-fluorophenyl)-1-methylnaphthalene (2i New Compoundmentioning
confidence: 99%
“…As illustrated in Scheme , they have been used as C2, C4, as well as C5 synthons for [2+ n ], [4+ n ], and [5+ n ] cycloaddition reactions, respectively, to construct highly functionalized polycyclic and heterocyclic compounds (Scheme ). However, to the best of our knowledge, using ortho -alkynyl benzyl alcohols as C6 synthons to access polysubstituted naphthalenes is seriously limited, especially under metal-free conditions. The main challenge may be attributed to the nucleophilic nature of the hydroxyl group at the benzyl position, which readily undergoes addition reactions with electrophilic groups to give oxygen-containing heterocyclic compounds (Scheme , path a and b). …”
Section: Introductionmentioning
confidence: 99%
“…All of these results show that both the size and the electronic nature of the substituent are essential factors for this [4+1] annulation reaction. 10,15 To further investigate the reaction scope, when we switched a-cyano-chalcone 1a to activated alkene 4a from 1,3-indandione and aldehyde, it was found that the annulation reaction of ninhydrin-derived carbonate 2a with alkene 4a was also completely switched to a classical b-regioselective [3+2] version of annulation under the same catalytic conditions, in which the [4+1] by-product was not detected, obtaining the polysubstituted cyclopentene 5a bearing dispiro-bisindanedione motifs in 72% yield. Additionally, the structural correctness of 5a was straightforwardly determined by single-crystal X-ray diffraction analysis (in Table 2, CCDC 2311772 †).…”
mentioning
confidence: 99%
“…All of these results show that both the size and the electronic nature of the substituent are essential factors for this [4+1] annulation reaction. 10,15…”
mentioning
confidence: 99%
“…6e Despite the achievement of 5H-dibenzo[a,d]cycloheptenes, the aforementioned protocols typically suffer from the requirements of multi-step manipulation, complex functionalized starting materials, noble metal catalysts, and a stoichiometric amount of ortho-Alkynyl benzyl alcohols, bifunctional compounds bearing hydroxy and alkynyl groups, are easily accessible and low-toxic synthons in organic synthesis, and have been recently employed as C2 or C4 synthons in [2 + n] or [4 + n] cycloaddition reactions, respectively. 7 However, to the best of our knowledge, the use of ortho-alkynyl benzyl alcohols directly as C5 synthons is seriously limited. Retrosynthetic analysis of the 5H-dibenzo [a,d]cycloheptene skeleton suggests that a straightforward and regioselective [5 + 2] annulation of ortho-alkynyl benzyl alcohols (C5 synthon) with arenes (C2 synthon) via sequential intermolecular Friedel-Crafts-type alkylation reaction and intramolecular 7-endo-dig cyclization reaction would be a promising alternative to the reported methods.…”
mentioning
confidence: 99%